Numerical simulation of heat and mass transfer of a wall containing micro-encapsulated phase change concrete (PCC) - Lajimi, Nour; Ben Taher, Nour; Boukadida, Noureddine (Frontiers in Environmental Science, 2023)
Before planning to equip buildings with energy systems, it is essential to first understand and control the behavior of the premises (via control of heat and water transfer phenomena) (air conditioners, heat pumps, heat exchangers, etc.). Given the amount of solar radiation to which it is exposed in summer and its significant contribution to energy loss in winter, the thermal insulation of the ceiling appears effective. The objective of this work is to study the heat and mass transfer through a ceiling wall containing micro-encapsulated phase change materials under realistic climatic conditions based on meteorological data in Tunisia. This article is about a numerical study that uses software (DIGITAL Visual FORTRAN 95) to predict the effect of incorporating a layer of PCM on thermal behavior, mass, and occupant thermal comfort, as well as energy consumption for summer and winter periods.